The Language of F. D. Roosevelt’s ‘Pearl Harbour Address to the Nation’ Persuasive Call to Arms Discourse: A Rhetorical Criticism - Yousif , Ghaidaa Fahmie; Mnaathar, Inas Malik (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this work is to analyze the representative speeches of F. D. Roosevelt with a view to getting some meaningful insight into the political oratory (call to arms) in general and of the speaker in particular. The focus of this work is on identifying various linguistic strategies used in 'Pearl Harbour Address to the Nation’ for realizing various persuasive strategies, intentions and sub-intentions. For doing so, a model of analysis has been developed to include Aristotelian and Brown and Levinson’s Politeness Theory. This is to understand F. D. Roosevelt’s rhetoric and politeness strategies, which they have used in persuading the masses and influencing their decisions. Hence, this work makes some meaningful observations about persuasive strategies and speech delivery styles of the said orator. In terms of findings, the analysis found that the major intention of the speech and speaker was to persuade the audience to change / affect their view or to take some action as intended by the orator (i.e., persuade the congress to declare war against Japan). Besides that, various strategies have been used to realize these sub/intentions. However, some of these strategies, intentions sub-intentions have been found interlinked, as they have mostly been found occurring together.